History in the eye of the beholder?: social location and allegations of racial/colonial biases in reconstructions of Sennacheribs invasion of Judah - Evans, Paul S. (The journal of Hebrew scriptures, 2012)
Studies by A.O. Bellis and H.T. Aubin have criticized scholars for failing to acknowledge the role of Africans in the ‘deliverance’ of Jerusalem from the Assyrian threat in 701 BCE due to racial bias and the continuing influence of 19th century colonial scholarship. This article examines their arguments in detail and demonstrates that the evidence does not support their hypothesis. Furthermore, this article considers to what extent social location as well as racial and political bias affect biblical scholarship, and particularly reconstructions of history.